Unforeseen occupational injury from textile foil printing machine: A case report exploring injury mechanism and forensic analysis (Journal of Forensic Medicine & Toxicology, 2025)
Despite significant efforts to enhance workplace safety, occupational injuries constitute a substantial proportion of  the overall injury burden globally. The textile industry is a prominent global industrial sector that utilises a variety of  machinery to transform fibres into cloth. This article reports an unusual case in which an injury was caused by a textile  hot foil printing machine, a device that is generally regarded as safe. A 40-year-old man suffered severe injury to his  upper limb while attempting to introduce fabric into the foil printing machine during the machine’s initial operation  time. The injuries are characterised by a combination of abrasion, laceration, crush injury, fracture, and avulsion. The  patient was treated surgically, and there was a significant physical and economic burden. Establishing the occurrence and  mechanism of injury is essential for raising safety awareness and reducing the likelihood of dangerous injuries among  stakeholders. In conclusion, this case report highlights the potential hazards associated with textile hot foil printing  machines, despite their apparent level of safety. Heightened awareness, protective measures, and comprehensive training  are pivotal to prevent such occupational hazards any industrial settings.
Keywords: Foil printing machine; Machine injury; Occupational accident; Health and safety; Hand injury